Kinerja Finansial Usaha Ternak Babi di Kecamatan Rahong Utara Kabupaten Manggarai - Lole, Ulrikus R.; Hari, Eldiana; Rosdiana Deno Ratu, Maria; Krova, Maria (Journal of Comprehensive Science, 2024)
A study was conducted in North Rahong District, Manggarai Regency. This research aims to analyze the income and financial feasibility of pig farming businesses in North Rahong District, Manggarai Regency. The sampling method is carried out in two stages. In the first stage, sample villages were determined from 12 villages, 4 sample villages were purposively determined by considering having the largest number of pigs. The second stage of determining sample breeders was carried out non-proportionately at random, where 15 respondents were taken from each village to obtain 60 respondents. Primary data was obtained through direct observation and interviews with breeders based on a list of questions that had been prepared, while secondary data was obtained through documented reports from relevant agencies and literature. The data analysis method is income analysis and financial analysis using the criteria for net investment B/C, BEP unit, BEP rupiah, and Payback Period. The research results show that the average total income is IDR 9,079,804.89/year, namely 37.61% is cash income and 62.99% is non-cash income. The results of the financial feasibility analysis show that the pig farming business in North Rahong District is financially feasible with a B/C value of 0.85, unit BEP of 0.33 ST, Rupiah BEP of IDR 3,200,999.78 and PP value of 1 year (12 month).